'Peri-urbanisation and loss of arable land': Indigenes' farmland access challenges and adaptation strategies in Kumasi and Wa, Ghana. (March 2023) - Sumbo, Dennis Kamaanaa; Anane, George Kwadwo; Inkoom, Daniel Kweku Baah
Abstract: Rapid urbanisation, particularly in Africa is leading to the transformation of peri-urban landscapes in several ways. In many instances, it affects indigenes of peri-urban communities and their access to farmland. Drawing from lived experiences among indigenes, traditional authorities, and planners in four peri-urban communities in two Ghanaian cities with differing tenure systems, Kumasi (a centralised society) and Wa (an acephalous society), this study used the case study strategy conducted through qualitative research to understand indigenes' farmland access challenges and adaptation strategies after former agricultural land is converted into peri-urban plots amid rapid urbanisation. The study revealed that rapid urban expansion has drastically reduced available land for farming in both acephalous and centralised case studies. In effect, indigenes who previously farmed on peri-urban lands are now adopting various strategies including moving to farther communities for agricultural land and off-farm retail businesses. However, these strategies were found to be ineffective for various reasons. The paper discovered emerging contestations between indigenes and peri-urban developers as the former sought to continuously use allocated plots for farming activities whereas the latter wanted to develop the same into other urban uses. The study further revealed that increasing peri-urbanisation and the attendant farmland losses were negatively affecting the wellbeing of indigenes that used to live on the proceeds from on-farm economic activities. The study recommends that land use planning in peri-urban areas should consider urban agriculture as an integral part of the urban land use process. Highlights: Municipal Wa more than tripled, Metropolitan Kumasi more than doubled in sizes in 30 years. Proximity to last allocated plot, not necessarily to physical development engenders conversion of farmland. In Pramso, less than one-fourth of farmland under conversion now exists for farming purposes. Male indigenes in acephalous cases accessed direct incomes from land allocation, unlike centralised counterparts.